Comparison of Dry and Flood Turning in Terms of Dimensional Accuracy and Surface Finish of Turned Parts - Rafai, Noor; Islam, Mohammad Nazrul (Springer, 2011)
This work presents experimental and analytical results of a comparison of dry and flood turning in terms of quality of turned parts. Subsequently, the influence of independent input parameters on quality characteristics is investigated in order to optimize their effects. Three techniques—traditional analysis, Pareto ANOVA analysis, and the Taguchi method—are employed. Hardened alloy steel AISI 4340 has been selected as work material. The results show that for certain combinations of cutting parameters, dry turning produced better dimensional accuracy compared to that produced by flood turning. Therefore, in the future, it will be possible to develop a system through modelling the cooling process that will be capable of predicting the situations where dry turning will be beneficial. This will reduce the application frequency of cutting fluids by avoiding their unnecessary applications and, consequently, their negative impact on the environment.